2016
DOI: 10.1007/s00224-016-9737-6
|View full text |Cite
|
Sign up to set email alerts
|

Genericity of Weakly Computable Objects

Abstract: In computability theory many results state the existence of objects that in many respects lack algorithmic structure but at the same time are effective in some sense. Friedberg and Muchnik's answer to Post's problem is one of the most celebrated results in this form. The main goal of the paper is to develop a general result that embodies a large number of these particular constructions, capturing the essential idea that is common to all of them, and expressing it in topological terms. To do so, we introduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The third observation of the kind described in the previous section (that asking a real number to be left-computable and nearly computable and to satisfy some other effectivity condition forces the number to be computable) that we wish to mention is the following result by Hoyrup [10].…”
Section: Nearly Computable Numbers a Genericity Notion And Randomness...mentioning
confidence: 92%
See 2 more Smart Citations
“…The third observation of the kind described in the previous section (that asking a real number to be left-computable and nearly computable and to satisfy some other effectivity condition forces the number to be computable) that we wish to mention is the following result by Hoyrup [10].…”
Section: Nearly Computable Numbers a Genericity Notion And Randomness...mentioning
confidence: 92%
“…For example, an argument by Downey, Hirschfeldt, and LaForte [5,Pages 105,106] shows that any strongly left-computable and nearly computable real number is even computable. In Section 8 we discuss three further results of the same type, one by Hoyrup [10] and two by Stephan and Wu [22]. Hoyrup [10] has shown that any nearly computable and left-computable number that is not computable is weakly 1-generic.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We apply this method to obtain a result in computable analysis related to the non-computability of the ergodic decomposition theorem. In [6] we give other applications of this method showing that many complicated constructions in recursion theory can be more easily obtained by choosing the suitable topology on the space of objects, and using the corresponding Baire Category theorem on that space.…”
Section: Other Classes Of Objectsmentioning
confidence: 99%
“…[10]). In a computable Polish space, a Π 0 2 -set is computably overt if and only if it contains a dense computable sequence.…”
mentioning
confidence: 99%